Detection of human case of dengue virus 2 belonging to sylvatic genotype during routine surveillance of fever in Senegal, Kolda 2021 - Dieng, Idrissa; Sagne, Samba Niang; Ndiaye, Mignane; Barry, Mamadou Aliou; Talla, Cheikh; Mhamadi, Moufid; Balde, Diamilatou; Toure, Cheikh Talibouya; Diop, Boly; Sall, Amadou Alpha; Fall, Gamou; Loucoubar, Cheikh; et al. (Frontiers in Virology, 2022)
A human case of dengue virus 2 (DENV-2) was detected from a febrile patient living in the Sare yoba, Kolda region (Southern Senegal). Phylogenetic analysis based on full coding region reveals that the virus belongs to the DENV2 Sylvatic genotype and is closely related to a strain (JF260983/ 99.66% identity) detected in Spain from a tourist who travelled to Guinee Bissau (bordering Kolda region) in 2009. This highlights a potential recent underreported circulation of sylvatic Dengue in the southern part of Senegal and calls for re-enforced integrated surveillance among humans, non-human primates and arboreal mosquitoes throughout a one-health approach.